Building on Shaky Ground. - Neville-Neil, George V. (Communications of the ACM, 2025)
This article addresses the CrowdStrike incident which highlighted critical failures in technology systems that impacted various sectors like travel, healthcare, and banking. Much of the article focuses on issues like poor testing and specific bugs as well as the deeper problem that lies in the fundamental architecture of current computer systems, which rely on unsafe languages and complex hardware. The author forwards a solution that calls for rethinking system design, implementing safer hardware architectures, and adopting type-safe programming languages like Rust to reduce vulnerabilities. Ultimately, he says, addressing these architectural flaws is essential for ensuring the safety and reliability of modern infrastructure, which increasingly underpins critical services worldwide.